2016
DOI: 10.1111/ctr.12853
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion with packed red blood cells while awaiting lung transplantation is associated with reduced survival after lung transplantation

Abstract: Blood transfusion while on the LTx wait list was associated with diminished patient survival after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Pretransplant RBC transfusion is also associated with both PGD as well as greater mortality. 19 A retrospective, propensity-matched US cohort study by Hayes et al 19 identified pretransplant transfusion as a risk factor for all-cause mortality at 1 year. The incidence of pretransplant transfusion was 34%, which was associated with an adjusted hazards ratio of 1.18.…”
Section: Transfusion and Primary Graft Dysfunction/acute Lung Rejectionmentioning
confidence: 99%
“…Pretransplant RBC transfusion is also associated with both PGD as well as greater mortality. 19 A retrospective, propensity-matched US cohort study by Hayes et al 19 identified pretransplant transfusion as a risk factor for all-cause mortality at 1 year. The incidence of pretransplant transfusion was 34%, which was associated with an adjusted hazards ratio of 1.18.…”
Section: Transfusion and Primary Graft Dysfunction/acute Lung Rejectionmentioning
confidence: 99%
“…exceeding 5 units and potentially when less than 2 units are given (Figure 2). While preoperative transfusion of PRBC in patients awaiting lung transplantation had been connected to reduced survival after lung transplantation by other investigators before, 27 intraoperative allogenic blood transfusion was found to have no undesirable impact on outcome among 310 lung transplantation recipients. 28,29 The risk for developing transfusion reactions might even be attenuated in this population, which could be due to suppression of immunological reactions by transfusion of irradiated PRBC and perioperative immunosuppression.…”
Section: Discussionmentioning
confidence: 93%
“…Of course, the need for transfusion was again just one of many high-risk variables in this cohort of patients. 10 That said, subsequent propensity matching was performed to control for these disparities and survival remained worse in the transfused cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies directly addressed the question of transfusion and lung transplant (Table 1). [6][7][8][9][10][11][12][13][14][15][16][17][18] Eleven of the 13 studies were single center and retrospective. Four studies reviewed center-specific interventions for reducing transfusion requirements specific to lung transplant patients.…”
Section: Study Characteristicsmentioning
confidence: 99%